THE INFLUENCE OF LEARNING ACCOMPANIED BY SELF HYPNOSIS ON INCREASING MATHEMATICS VALUE - Susdarwono, Endro Tri (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2021)
Hypnosis is the fastest and most effective way to get into the subconscious mind. Each suggestion was nine times stronger than the usual situation. This experimental research aims to provide a description of the effect of learning accompanied by self-hypnosis on increasing mathematics scores. The test is done by comparing the post-test scores of the control group and the experimental group through the t test for the independent sample. This experimental study concluded that the method of learning mathematics with self-hypnosis was able to improve students' mathematical abilities. This conclusion is evidenced by the significant difference between the mean of group 1 as the control variable and group 2 as the experimental variable after being given treatment or stimulus for a period of 1 semester